H.L.A. Hart - MacCormick, Neil (Jurists-- profiles in legal theory., 2008)
In this substantially revised second edition, Neil MacCormick delivers an introduction to the life and works of H.L.A. Hart noted Professor of Jurisprudence at Oxford University from 1952 to 1968. The work includes Hart's ideas on the theory of legal rules, legal reasoning, judicial discretion, the social sources of law, and more.